A Novel High-Gain Circularly Polarized Filtenna Based on Coaxial Structure - Zhang, D.; Zhu, K.; Qi, S. (Radioengineering Society, 2025)
A novel omnidirectional slot array filtenna with a circularly polarized (CP) radiation beam is presented in this paper. This filtenna utilizes the coaxial cylinder structure, and the antenna’s filtering function is primarily achieved through the direct synthesis method of a tubular bandpass filter. Four perpendicular slot pairs form the basic omnidirectional CP radiation element, which is cut into the sleeve and added to the outer conductor of the coaxial cylinder to implement the compact performance. To simplify the design, this work utilizes the high and low impedance conversion of the inner conductor, as well as isolation through dielectric materials. This filtenna achieves high gain by forming an array along the z-axis direction and placing the antenna elements reasonably for radiation in phase. A prototype was designed and fabricated to validate its practicality. The results indicate a fractional impedance bandwidth (S11 less than -10 dB) of 5.8%, from 8.87 GHz to 9.39 GHz, and a 3 dB axial-ratio (AR) bandwidth of 6.1%, from 8.85 GHz to 9.40 GHz. The realized gain of the antenna is consistently higher than 5.29 dBi over the operating bandwidth, and its out-of-roundness is less than 1.5 dB in the radiation direction.
Keywords: Circular polarized (CP) filtenna; filtering antenna; axial ratio (AR); omnidirectional antenna; tubular bandpass filter